THU0547 Evaluation of Venous Disease Spesific Quality of Life in Patients with Vascular Behçet's Disease. (9th June 2015) - Alibaz-Oner, F.; Aldag, B.; Aldag, M.; Unal, A.U.; Toptas, T.; Ergun, T.; Direskeneli, H.
Abstract : Background: Vascular involvement especially in young males and is one of the major causes of mortality and morbidity. Lower extremity deep vein thrombosis (DVT) is the most frequent form of vascular involvement. Chronic post-thrombotic syndrome develops in up to one-half of patients with deep venous thrombosis. Patients with post-thrombotic syndrome have substantially impaired quality of life. Objectives: There is no data about post-thrombotic syndrome in deep venous thrombosis associated with Behçet's Disease. In this study, we aimed to evaluate venous disease spesific quality of life in patients with Vascular Behçet's Disease (VBD). Methods: In this study, 62 patients (Male/Female: 47/15, mean age: 38.6±9.2 years) with VBD, who were regularly followed in Marmara University Behçet clinic, 29 patients (Male/Female: 20/9, mean age: 41.6±11.8 years) with DVT associated with non-BD reasons, who were followed in Hematology and Vascular Surgery Department, were assessed. Venous Disability Score (VDS) and Venous Clinical Severity Score (VCSS) were used to evaluate the severity of venous insufficiency. Venous disease-specific quality of life (the primary outcome) was measured using the Turkish validated form of Venous Insufficiency Epidemiological and Economic Study Quality of Life/Symptom questionnaire (VEINES-QoL/Sym). After calculation, VEINES-QoL and VEINES-Sym sub-score were identified. Higher score shows better QoL. Short Form (SF-36) and Behçet Syndrom Activity Score (BSAS) questionnaire were also fullfilled to patients. Results: Physical and mental component of SF-36 were similar between VBD and non-BD group. VCSS and VDS were significantly worse in non-BD group compared to VBD. VEINES-QoL and VEINES-Sym were significantly better in VBD group (Table 1 ). Mean duration after DVT was 6.7±5 years in VBD, 1.6±1 years in non-BD group. There was no correlation between VEINES-QoL, VEINES-Sym score and duration after DVT, daily sitting and standing time. But VEINES-QoL and VEINES-Sym negatively correlated with VCSS (respectively; r: -0.367, p<0.001, r:-0.384, p<0.001) and VDS (respectively, r: -0.288, p=0.007, r:-0.265, p=0.013). VEINES-Sym and VEINES-QoL also significantly correlated with BSAS (respectively, r: -0.526, p<0.001 ve r:-0.496, p<0.001). Conclusions: In our study, we found that venous spesific QoL and symptoms worsen together with increasing VDS and VCSS score. These results suggest that controlling of disease activity increase the OoL as well as preventing the relapses. Disclosure of Interest: None declared